Pengukuran Indeks Kepuasan Layanan Infrastruktur (IKLI) di Kabupaten Banyumas Tahun 2025 - Ariq Cahya Wardhana; Atik Munggiarti; Yatin Ciptaningrum (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2026)
The 2025 Infrastructure Service Satisfaction Index (IKLI) measurement for Banyumas Regency shows that the IKLI achievement is at 3.56 or 71.02 points with a category B (Good), which reflects public satisfaction with infrastructure services is quite good but not evenly distributed. The dimension with the highest achievement is Public Service (3.93), while Public Space (3.18) is the lowest, indicating disparities between dimensions. The results of the Gap Analysis identified the greatest mismatch between expectations and reality in the Public Space dimension. The IPA and PGCV analysis placed Public Space, Transportation, Irrigation, and Housing as the top priority (Quadrant I). In conclusion, policy interventions need to be focused on these priority sectors while maintaining the quality of the Public Service dimension that has been good.